The Influence of Romantic Relationships on Substance Use in Emerging Adulthood. (October 2018) - Angulski, Kate; Armstrong, Todd; Bouffard, Leana A.
The current work built on prior research showing aspects of romantic relationships, including relationship quality and partner substance use, influence individual risk for substance use during emerging adulthood. Analyses were based on a sample of males from the Pathways to Desistance Project (PDP) data. Romantic relationships were quantified with an aggregate measure of relationship quality and specific measures of relationship satisfaction, monitoring, and partner antisocial behavior. With a focus on emerging adulthood, the current work was centered on Waves 8 and 9 of the PDP data. Regression models tested the association between the relationship measures and alcohol intoxication, marijuana use, and hard drug use in the past year. Models considered both contemporaneous and longitudinal effects. Across the aspects of romantic relationships, monitoring and partner antisocial behavior had the most consistent association with substance use. The association between monitoring and substance use was strongest when longitudinal effects were tested among those in a relationship at both Waves 8 and 9. Peer antisocial behavior and prior substance use were also associated with substance use. Results show that romantic relationships have an important influence on substance use within a criminal justice involved sample.